Od fryzjera do bibliotekarza. Niezwykłe losy Feliksa Dłubka (PDF 1,85 MB) (Książnica Śląska, 2025)
The article is devoted to Feliks Dłubek, the first employee of theBiblioteka Sejmu Śląskiego, later of the Śląska Biblioteka Publicznaand the Biblioteka Śląska. The author, on the basis of archival handwritten materials, reconstructs the biography of the librarian, evoking numerous facts from his life: his work as a hairdresser assistantin Germany, France and Great Britain, his service in Haller’s armyduring WW1, his pro-Polish activity during the plebiscite in UpperSile-sia and his many years of employment as a librarian.